Molecular Mechanisms of Mutations in Factor XIII A-subunit Deficiency: In vitro Expression in COS-cells Demonstrates Intracellular Degradation of the Mutant Proteins - Palotie, Aarno; Mikkola, Hanna; Muszbek, Laszlo; Haramura, Gizela; Hämäläinen, Eija; Jalanko, Anu (Thrombosis and Haemostasis, 1997)
Factor XIII deficiency is an autosomal recessive bleeding disorder that is largely caused by various mutations in FXIII A-subunit gene. Characteristically, the patients lack both A-subunit activity and antigen in the circulation. Here we have analysed the consequences of four mis-sense mutations (Met242→Thr, Arg252→Ile, Arg326→Gln, Leu498 to Pro) and one stop mutation (Arg661→Stop) in the FXIII A-subunit gene by expression in COS-cells. After transient transfection each mutant cDNA expressed mRNA at an equal level to the wild type FXIII. However, the mutant polypeptides accumulated in the cells in significantly reduced quantities and demonstrated only very low enzymatic activity. Analysis of immunoprecipitated metabolically labelled polypeptides demonstrated remarkable instability and intracellular degradation of all mutant FXIII proteins. These results verify the deleterious nature of the individual amino acid changes and confirm that protein instability and susceptibility to proteolysis are consequences of the mutations, as predicted from the three-dimensional model of crystallised FXIII A-subunit.